Effects of carrier frequency accuracy on quasi-synchronous, multicarrier DS-CDMA communications using optimized sequences. - Kun-Wah Yip (IEEE Journal on selected areas in communications)
It is known that the multiple access interference (MAI) of a quasi-synchronous (QS) multicarrier direct signal code division multiple access (DS-CDMA) system can be substantially reduced by using signature sequences having optimized cross correlation at small shifts around the origin. This paper shows that the time-frequency cross correlation function rather than the usual (time-domain) cross correlation determines the MAI when the system is operated in the presence of carrier frequency offset (CFO), which arises due to the frequency-accuracy limit of the oscillator. Several known sets of sequences having optimized time-domain cross correlation are investigated for their MAI-minimization capabilities in the presence of CFO. It is found that: (i) a system using Walsh codes or Suehiro-Hatori (1985) polyphase sequences can be driven into outage as a result of significant worst-case MAI and (ii) it is possible to minimize the MAI for systems using preferentially phased Gold codes cyclic-shift m-sequences or Lin-Chang 9see ibid., vol.45, p.221-6, 1997) sequences only if the product of chip period and maximum frequency deviation is less than around 0.01. Implications of these findings to practical implementation of systems are discussed